EFEKTIVITAS HUKUM PERMA NO 1 TAHUN 2019 TENTANG ADMINISTRASI PERKARA DAN PERSIDANGAN DI PENGADILAN SECARA ELEKTRONIK DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA GUNUNG SUGIH LAMPUNG TENGAH - Mahdalena, Mahdalena; Zuhraini, Zuhraini; Nurnazli, Nurnazli (Mabahits : Jurnal Hukum Keluarga Islam, 2025)
Abstract This study examines the E-litigation Trial process in divorce cases at the Gunung Sugih Religious Court, the effectiveness of the implementation of Perma Number.1 of 2019 concerning Electronic Litigation Administration and Trials in Divorce Cases at the Gunung Sugih Religious Court, Central Lampung Regency. This research is a field research, which was conducted at the Gunung Sugih Religious Court, Central Lampung, the primary data in this study were obtained through documentation and interviews with judges at the Gunung Sugih Religious Court, and the secondary data consisted of books, journals, which were in accordance with the research topic. , then in this study it was analyzed using two theories, namely the theory of effectiveness and the theory of maslahah mursalah. The results of the research in this study are that the implementation of e-litigation trials at the Gunung Sugih Religious Court has been effective and efficient, because by implementing e-litigation it will be much easier in order to realize the principles of religious courts, namely simple, fast process and low cost. Then, to be more optimal, there must be improvements regarding tools and equipment such as internet networks and the necessary devices. If we look at the positive impacts of having an electronic trial or e-litigation, it will be more beneficial if the trial is carried out via e-litigation, for parties who are out of town, with several examples such as divorce lawsuits if the parties are abroad. Then if the trial process during the Covid-19 pandemic is via e-litigation, it will create benefits, namely preserving the souls of the parties, legal advisors and court officials, considering that we must avoid and break the chain of transmission of Covid-19, then by seeing that there were several incidents in the trial, the trial via e-litigation is also in order to preserve the souls of the parties from incidents that can endanger the parties. Keywords: Legal Effectiveness, e-litigation, divorce cases